POLA PERMUKIMAN KAMPUNG ADAT LEWOHALA DI KABUPATEN LEMBATA-FLORES PROVINSI NUSA TENGGARA TIMUR - Payong, Yohannes Kapistranus Sasong (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 3 No 2 (2016): Agustus 2016DO - 10.24843/JRS.2016.v03.i02.p08, 2016)
Kampung Adat Lewohala is a traditional settlement with distinctive representation of its historical development. Communal spaces and other elements have been constructed following conventions and belief with adaptation to the natural environment. So the main aim of the following qualitative research has been to identify and gain comprehension of the organizational elements composing the Lewohala settlement. This study primarily addresses the entry points of Bawa Lowe which are located in four different aspects of settlement; as well as the core called Lewu kepuhur . In addition, there exists a public open space ( nawang ) defined by the houses of lango adat . This core area also accommodates kako as a place to entertain and demonstrate hospitality; wule - a traditional market; and belinda nore – special storage to keep weapons. What emerges from this study is the suggestion that the human body is reflected by symbolic representation in the pattern of the whole settlement. Keywords: Kampung Adat Lewohala; settlement pattern; elements of settlement Abstrak Kampung Adat Lewohala merupakan desa tradisional yang merepresentasikan perkembangan kesejarahan yang berbeda dengan desa lainnya. Ruang-ruang komunal dan elemen lainnya dikonstruksikan mengikuti aturan adat dan sistem kepercayaan yang diadaptasikan pada lingkungan alamiah desa tersebut. Tujuan penulisan ini adalah untuk mengidentifikasi dan memperoleh gambaran lengkap tentang pengorganisasian elemen yang membentuk permukiman Lewohala . Studi ini terutama ditujukan kepada Bawa Lowe yang terletak di empat aspek berbeda dari permukiman tersebut, juga sebagai kawasan inti dari permukiman Lewu Kepuhur . Selain itu, keberadaan ruang terbuka (nawang) yang didefinisikan sebagai rumah lango adat . Kawasan inti ini juga mengakomodasi kako sebagai tempat untuk mempertunjukkan ikatan kekeluargaan mereka; wule – pasar tradisional; dan belinda nore – ruang penyimpanan khusus untuk senjata. Hasil studi ini memperlihatkan bahwa keseluruhan pola permukiman desa adat ini merupakan refleksi simbolik dari tubuh manusia.
Keywords: Kampung Adat Lewohala, pola permukiman, elemen-elemen permukiman